Gadai Syari'ah Di Indonesia : Konsep, Implementasi Dan Institusionalisasi - ANSHORI, Abdul Ghofur (Gadjah Mada University Press, 2006)
Gadai Syari'ah Di Indonesia : Konsep, Implementasi Dan Institusionalisasi